Multidestination travel of the Slovenian population - Cigale, Dejan (Bulletin of Geography. Socio-economic Series, 2020)
This paper focuses on the multidestination travel of the Slovenian population. It presents the results of a questionnaire survey that aimed to gain insight into some relevant characteristics of the travel behaviour of the Slovenian population and its links to factors that were found in previous research to be related to the incidence of multidestination travel. A destination was defined within this research as any location where an overnight stop is made. Single-destination trips prevailed. Still, a considerable percentage of respondents’ most recent trips had been multidestination trips. The greater part of them was directed to just one country within which they visited several overnight destinations. The results indicate that duration of trip, distance of destination from tourists' residential location, familiarity of destination, travel-group size and tourists' activities are associated with the likelihood of multidestination travel.